The Effectiveness Of Internal Control And The Implementation Of Governance And Its Impact On The Performance Of Regional Head - Anthon S.Y. Kerihi; Yohanes Demu; Herly M. Oematan (Green Publisher Indonesia, 2021)
Accurate regional financial management, transparency, and accountability are urgent needs in the framework of the implementation of clean and responsible local government in order to achieve good governance. Internal control is designed to provide adequate confidence about the achievement of three dimensions: effective and efficient, accountability reports and compliance with applicable provisions. This research aims to know and analyze: 1) the effect of the effectiveness of internal control on the performance of regional heads, 2) the influence of governance implementation on the performance of regional heads and 3) the effect of the effectiveness of internal control and the simultaneous implementation of governance on the performance of regional heads. This type of research is quantitative research. The sampling technique in this study is purposive sampling using a sample of 15 SKPD in Kupang Regency. OPD and each OPD selected 3 respondents (head of OPD, Finance section and Banwas) so that 45 respondents were obtained. The data collection techniques in this study used questionnaires. The data analysis technique in this study used multiple linear regression analysis. The data sources used are primary data and secondary data. The results of this study show that 1) the effectiveness of internal control affects the performance of regional heads in the Kupang Regency Government, 2) The implementation of government governance affects the performance of regional heads in the Kupang Regency Government, and 3) The effectiveness of internal control and the implementation of government governance affect simultaneously on the performance of the kupang regency government.